2021
DOI: 10.7150/thno.55482
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous glutamate determines ferroptosis sensitivity via ADCY10-dependent YAP suppression in lung adenocarcinoma

Abstract: Rationale: Ferroptosis, a newly identified form of regulated cell death, can be induced following the inhibition of cystine-glutamate antiporter system X C - because of the impaired uptake of cystine. However, the outcome following the accumulation of endogenous glutamate in lung adenocarcinoma (LUAD) has not yet been determined. Yes-associated protein (YAP) is sustained by the hexosamine biosynthesis pathway (HBP)-dependent O-linked beta-N-acetylglucosaminylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 110 publications
(109 citation statements)
references
References 64 publications
5
104
0
Order By: Relevance
“…Therefore, we believe that in future clinical treatment, using ferroptotic therapy to treat drug-resistant patients or using ferroptotic therapy directly in combination with chemotherapy or targeted drugs can effectively avoid tumor progression caused by drug resistance. In addition, several ferroptotic sensitivity biomarkers (such as ACSL4, calcium/calmodulin-dependent protein kinase kinase 2 (CAMKK2) and ADCY10 (Doll et al, 2017;Wang et al, 2021;Zhang et al, 2021)) and therapeutic targets (such as FTL and YAP (Wu et al, 2019;Zhang et al, 2021)) have been identified, all of which provide support for ferroptosis use in clinical oncology therapy. Of course, although ferroptotic-promoting drugs such as sorafenib have been applied in clinical tumor treatment (Chen et al, 2021), the extensive application of ferroptotic therapy in clinical studies requires the guidance of clinical studies with large sample sizes and multicenter and finely grouped specimens.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we believe that in future clinical treatment, using ferroptotic therapy to treat drug-resistant patients or using ferroptotic therapy directly in combination with chemotherapy or targeted drugs can effectively avoid tumor progression caused by drug resistance. In addition, several ferroptotic sensitivity biomarkers (such as ACSL4, calcium/calmodulin-dependent protein kinase kinase 2 (CAMKK2) and ADCY10 (Doll et al, 2017;Wang et al, 2021;Zhang et al, 2021)) and therapeutic targets (such as FTL and YAP (Wu et al, 2019;Zhang et al, 2021)) have been identified, all of which provide support for ferroptosis use in clinical oncology therapy. Of course, although ferroptotic-promoting drugs such as sorafenib have been applied in clinical tumor treatment (Chen et al, 2021), the extensive application of ferroptotic therapy in clinical studies requires the guidance of clinical studies with large sample sizes and multicenter and finely grouped specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we reported that FTH transcription first increased and then decreased after erastin treatment (Zhang et al, 2021). So how did FTL change after erastin was added?…”
Section: Ferritin Light Chain and Ferritin Heavy Chain Are Differentially Regulated After Erastin Treatmentmentioning
confidence: 95%
See 3 more Smart Citations